2012
DOI: 10.1074/mcp.m111.011114
|View full text |Cite
|
Sign up to set email alerts
|

DNA and Chromatin Modification Networks Distinguish Stem Cell Pluripotent Ground States

Abstract: Pluripotent stem cells are capable of differentiating into all cell types of the body and therefore hold tremendous promise for regenerative medicine. Despite their widespread use in laboratories across the world, a detailed understanding of the molecular mechanisms that regulate the pluripotent state is currently lacking. Mouse embryonic (mESC) and epiblast (mEpiSC) stem cells are two closely related classes of pluripotent stem cells, derived from distinct embryonic tissues. Although both mESC and mEpiSC are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 57 publications
1
10
0
Order By: Relevance
“…Indeed, measurement of glycolytic activity by the percentage of glucose converted to lactate revealed that ϳ40% of glucose was converted to lactate in WT EBs (Fig. 5D), whereas undifferentiated WT ESCs consumed ϳ80% of glucose for glycolysis, indicating that WT EBs experienced a metabolic switching during differentiation in agree- ment with a previous study (46). In contrast, the majority of glucose (ϳ95%) was still converted to lactate in Cited2 ⌬/Ϫ EBs (Fig.…”
Section: Increased Glycolytic Activity and Impaired Hypoxic Differentsupporting
confidence: 42%
“…Indeed, measurement of glycolytic activity by the percentage of glucose converted to lactate revealed that ϳ40% of glucose was converted to lactate in WT EBs (Fig. 5D), whereas undifferentiated WT ESCs consumed ϳ80% of glucose for glycolysis, indicating that WT EBs experienced a metabolic switching during differentiation in agree- ment with a previous study (46). In contrast, the majority of glucose (ϳ95%) was still converted to lactate in Cited2 ⌬/Ϫ EBs (Fig.…”
Section: Increased Glycolytic Activity and Impaired Hypoxic Differentsupporting
confidence: 42%
“…In this regard, it was postulated that conventional human ESCs might bear a greater resemblance to the mouse epiblast stem cells (EpiSCs), which originate from a developmentally more advanced post-implantation epiblast that has undergone X chromosome inactivation and cannot efficiently form germline chimeras when injected into blastocysts (Brons et al, 2007;Tesar et al, 2007). This diminished potency may be due to the differences in transcriptional and chromatin constituency between mouse EpiSCs and ESCs (Song et al, 2012).…”
Section: Distinct Pluripotency States Are Influenced By Extracellularmentioning
confidence: 99%
“…Interestingly, ESC-derived TSClike cells fail to acquire genomic methylation features of TSCs [21], arguing that epigenetic differences between ESCs and EpiSCs could limit the developmental potential of EpiSCs to become TSCs. Differences in the transcriptomes, proteomes, and chromatin states of ESCs and EpiSCs have been compared [62][63][64][65]. Notably, NuRD-dependent methylation prevents ESCs from spontaneously acquiring trophoblast fate [66][67][68][69].…”
Section: Figmentioning
confidence: 99%